Proposed Business Platform Model for Market Expansion using SEO Technique in Google Web Platform - Setiawan, Gaudensius Winsen; Astanti, Ririn Diar; Ai, The Jin (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2024)
Traditional business models consider physical assets such as shops, factories, and offices important in generating the company's revenue. This situation also occurs when a company tries to expand its market. For market expansion, using the traditional business model, the company tends to consider opening several sales office branches to support sales. It has consequences for generating additional costs for the company. With the advanced development of information technology, such as the Internet, customers can be reached through e-market platforms. Therefore, the research presented in this paper proposes a platform business model that can support market expansion without adding additional physical assets to the company. This research hypothesizes that developing websites using local language can help the company gain visitors from the area where it is trying to expand its market. Therefore, in the proposed platform business model supported by a website, it is recommended that the website be developed using the local language to expand the market without adding physical assets such as a sales office. The proposed platform business model is then implemented at PT. D&W International, which has been exporting products overseas since 2005. Using the proposed platform business model, the company develops the websites in three different languages: English, Portuguese, and Spanish. The result shows that the platform business model of using a website supported by local language effectively supports the company's business expansion.